DATA of 'Quantification of seasonal and diurnal dynamics of subglacial channels using seismic observations on an Alpine Glacier.' from Nanni et al. 2020 - Nanni, Ugo; Gimbert, Florent; Vincent, Christian; Gräff, Dominik; Walter, Fabian; Piard, Luc; Moreau, Luc (Zenodo, 2020)
This dataset belongs to the study of Nanni et al., 2020 "Quantification of seasonal and diurnal dynamics of subglacial channels using seismic observations on an Alpine Glacier." accepted for publication in The Cryosphere on March 9th 2020. You can find additional information on the " README_data_NANNI_2020_glacier " This work was supported by the SEISMORIV project (ANR-17-CE01-0008) and the SAUSSURE project (ANR-18-CE01-0015) funded by the Agence National de la Recherche (ANR).